Imaging the C black formation by acetylene pyrolysis with molecular reactive force field simulations1. Issue 17 (7th May 2015) - Zhang, Chaoyang; Zhang, Chi; Ma, Yu; Xue, Xianggui
<x xml:space="preserve">Abstract</x> Formation of C black undergoes four main stages: chain elongation, chain branching, cyclization and cycle-condensation, and folding of condensed cycles.